Cytopathology of Soft Tissue and Bone Lesions - Khalbuss, Walid E.; Parwani, Anil V.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2011)
Cytopathology Soft Tissue and Bone Lesions by Walid E. Khalbuss and Anil V. Parwani will fulfill the need for an easy-to-use and authoritative synopsis of soft tissue and bone cytopathology. This volume, part of the Essentials in Cytopathology book series, fits into the lab coat pocket and is ideal for portability and quick reference. Each volume in the series is heavily illustrated with a full color art program, while the text follows a user-friendly outline format. Walid E. Khalbuss, MD, PhD, FIAC is Associate Professor of Pathology at the University of Pittsburgh Medical Center - Shadyside Hospital, Pittsburgh, Pennsylvania. Anil V. Parwani, MD, PhD, is Associate Professor of Pathology at the University of Pittsburgh Medical Center - Shadyside Hospital, Pittsburgh, Pennsylvania.
Preface -- Fine Needle Aspiration Cytology (FNAC) of Soft Tissue Lesions: Basic Information and a Practical Approach -- The Value of Fine Needle Aspiration Cytology (FNAC) -- Cytopathology of Soft Tissue Lesions with Predominance of Spindle Cells -- Cytopathology of Soft Tissue Lesions Containing Giant Cells -- Cytopathology of Myxoid Soft Tissue Lesions -- Cytopathology of Soft Tissue Lesions with Predominance of Epithelioid, Round/Polygonal Cell, Glandular Cells, Inflammatory Cells -- Cytopathology of Lipomatous Soft Tissue Tumors -- Role of Imprint Cytology Intraoperative Diagnosis of Soft Tissue Lesions -- Ancillary Techniques in The FNAC of Soft Tissue Lesions -- Index.
Keywords: Pathology; Pathology